2019
DOI: 10.1175/wcas-d-18-0074.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change–Related Heat Stress and Subjective Well-Being in Australia

Abstract: There is mounting evidence that climate change impacts compromise people’s well-being. Many regions of Australia have experienced record hot temperatures and more frequent and longer heat waves with substantial consequences for people, economies, and ecosystems. Using data from an Australia-wide online survey with 1101 respondents, we investigated the relationship between self-reported measures of heat stress and different dimensions of subjective well-being. After controlling for socioeconomic factors known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
1
13
0
1
Order By: Relevance
“…For the ecological environment, although the comprehensive evaluation index in 2016 was slightly higher than that in 2007, the fluctuation during the decade was intense, especially in 2011. It then showed a turning point and reached its lowest point in 2013, which is basically consistent with the trend of the ecological environment pressure calculated by Zander et al in 2019 [24]. In recent years, the Australian Government has integrated the protection of the ecological environment into its national strategy.…”
Section: Trend Of Comprehensive Evaluation Indexsupporting
confidence: 85%
“…For the ecological environment, although the comprehensive evaluation index in 2016 was slightly higher than that in 2007, the fluctuation during the decade was intense, especially in 2011. It then showed a turning point and reached its lowest point in 2013, which is basically consistent with the trend of the ecological environment pressure calculated by Zander et al in 2019 [24]. In recent years, the Australian Government has integrated the protection of the ecological environment into its national strategy.…”
Section: Trend Of Comprehensive Evaluation Indexsupporting
confidence: 85%
“…Exposure to heat during work can reduce labour capacity and result in decreased productivity. Recent Australian research investigating the relationship between self‐reported heat stress and subjective wellbeing showed that many people thought that heat compromised their productivity . Last year, we reported on the combined effects of temperature and humidity on hours of labour lost, captured in what is referred to as the wet bulb globe temperature.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…Recent Australian research investigating the relationship between self-reported heat stress and subjective wellbeing showed that many people thought that heat compromised their productivity. 23 Last year, we reported on the combined effects of temperature and humidity on hours of labour lost, captured in what is referred to as the wet bulb globe temperature. This year, we calculated annual total hours of labour lost due to heat in the agriculture, industry and service sectors in Australia from 2000 to 2018 using an indicator that also includes the impact of sunlight on work hours lost (Box 7).…”
Section: Change In Labour Capacitymentioning
confidence: 99%
“…Así, los fenómenos climáticos tienen gran incidencia en la calidad de vida de las personas debido a que impactan el entorno que habitamos, estableciendo un factor de riesgo e inestabilidad añadida (9) , que genera, en las personas, inseguridad por el futuro e insatisfacción con la vida (10) . Cabe mencionar que la Organización Mundial de la Salud (OMS) y la Organización Panamericana de la Salud (OPS) establecen como grupos vulnerables al cambio climático a menores de 5 años, mujeres embarazadas o que amamantan, adultos mayores, pobres y las poblaciones excluidas socialmente en zonas urbanas y rurales (8,11) .…”
Section: Introductionunclassified